Effects of a Plant-Based Additive on the Properties of Flour and Dough during Fermentation - Alexander V. Maslov; Zamira Sh. Mingaleeva; Timur A. Yamashev; Oksana V. Starovoitova (Техника и технология пищевых производств)
To ensure a balanced diet, bakers use plant-based raw materials with a high nutritional value which affect the properties of flour and dough. We aimed to study the effects of a complex additive based on plant components on wheat flour’s amylolytic activity and gas-forming ability, as well as on the dough’s rise and gas-retaining ability during fermentation. Our study objects included premium wheat flour, a water-flour suspension, and wheat dough with a complex additive (at concentrations of 10, 16, and 22% by weight of flour mixtures). The additive contained whole wheat flour, crushed sprouted spelt, powdered pumpkin seeds, oyster mushrooms, and gooseberries at a ratio of 56.3:25.0:17.2:0.9:0.6, respectively. An amylograph-E was used to study the viscosity of the water-flour suspension during heating, an ICHP-1-2 apparatus measured the falling number, and an F4 rheofermentometer assessed the flour’s gas-forming ability and the dough’s rise and gas-retaining ability. The complex additive improved the enzymatic activity of the flour, increased the dough rise by an average of 8.4 mm, and reduced the fermentation time needed to reach the maximum height by an average of 17.8%, compared to the control. The total volume of carbon dioxide, as well as the volumes of lost and retained carbon dioxide, increased by an average of 35.8, 99.7, and 26.9%, respectively, compared to the control. The optimal concentration of the complex additive introduced into premium wheat flour was 16%, at which the dough rose to its maximum height and had the longest porosity time. To obtain high-quality products with this concentration of the additive, the total time of dough fermentation and proofing should be reduced by 17.8% compared to the unfortified dough. The results can be used in the production of bakery products from premium wheat flour fortified with the complex additive based on plant components. During the process, it is important to determine the duration of dough maturation and reduce the total time of dough fermentation and proofing depending on the concentration of the additive. Further research is needed to study the effect of the complex additive on the structural and mechanical properties of dough during its development.